Validitas, Kepraktisan, dan Efektivitas Bahan Ajar Berbantuan Google Sites pada Materi Getaran, Gelombang, dan Bunyi - Rahma Ramadanti Yusuf; Tirtawaty Abdjul; Citron S. Payu (Ideas Publishing, 2023)
One way to create interesting teaching materials is to design teaching materials with the help of a website by utilizing the Google Sites website builder application. This study aims to describe the validity, practicality and effectiveness of teaching materials assisted by Google Sites on Vibration, Waves and Sound. This research refers to the 4-D model development research which consists of the Define, Design, Develop and Disseminate stages. The results showed that the validity of teaching materials was included in the valid criteria, the practicality of teaching materials was classified as good criteria, the effectiveness of teaching materials in terms of student activities was classified as good criteria and from the learning outcomes of students, it was classified as medium N-gain criteria. Thus, the Google Sites-assisted Teaching Materials developed are valid, practical and effective for use in the learning process.